Internalized Homophobia and Coming out Process in Adolescence: A Case Report - Set, Zeynep (Eastern Journal of Medical Sciences, 2018)
For homosexual individuals, on the basis of self-directed homophobic attitudes and difficulties experienced during the coming out process, their society’s heterosexual and homophobic attitudes are specifically considered to play an essential role. Numerous difficulties and pressures in reconciling our differences, depending on various reasons, may lead to the increase in some psychopathologies of homosexuals compared to heterosexual individuals. Additionally, individuals with different sexual orientations, instead of a dominant heterosexual orientation, may face several challenges such as the process of coming out. Relative to heterosexuals, these individuals are supposed to explore, define and explain themselves in this sense. This study focuses on how mental health professionals can help adolescents to manage their coming out process through affirmative and positive therapeutic interventions. A case report was presented in order to examine the responses given to individuals with different sexual orientations i.e. how the individuals internalize these responses, the adverse effects of this internalization on mental health, models explaining the development of homosexual identity in adolescence and how these issues can be practiced in therapeutical settings.